The multiple faces of heparin: opportunities in COVID-19 infection and beyond - Drouet, Ludovic; Harenberg, Job; Torri, Giangiacomo (Thrombosis and haemostasis, 2020)
Thieme E-Books & E-Journals
Gesehen am 09.10.2025